SINTESIS SENYAWA ANTARA BENTUK ALKOHOL UNTUK TURUNAN ANTIBIOTIK C-9154 DARI MINYAK KULIT LAWANG - Healthy Kainama; Hardjono Sastrohamidjojo; Jumina Jumina (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2011)
It has been done the synthesis of pyperonil alcohol and Vanilil alcohol as precursor in derivative of C-9154 antibiotic from cullilawan oil. Safrole and eugenol is aim components was isolated from cullilawan oil with strong base NaOH. The synthesis was started by isomerisation of safrole with KOH in ethanol at reflux for 8 hours, then oxidation of isosafrole with KMnO4 using Tween 80 as the catalist in acid at 30oC for 15 minutes to give pyperonal. The further experimental stages were reduction of pyperonal with NaBH4 afforded pyperonil alcohol in 90% yield. Isomerisation of eugenol in KOH-ethanol for 8 hours at 180oC and further with acetylation of isoeugenol for protection of hydroxi group. Oxidation of isoeugenyl acetate use KMnO4 and polysorbic 80 as catalist in acid then hydrolisis in 69,4% vanilin. Reduction of vanilin by NaBH4 to give 85% vanilin alcohol. The purity of the products was determined using GC, whereas their structures were elucidated using FTIR, 1HNMR and MS